Structural properties of amorphous diamond-like carbon: percolation, cluster, and pair correlation analysis - Kowalczyk, Piotr; Gauden, P.; Terzyk, A. (Royal Society of Chemistry, 2012)
A detailed atomistic model of amorphous diamond-like carbon was developed combining experimental neutron scattering data (K. W. R. Gilkes, P. H. Gaskell and J. Robertson, Phys. Rev. B, 1995, 51, 12303) with the hybrid reverse Monte Carlo method. From the experimentally consistent nanoscale model of the disordered tetrahedral carbon we computed various properties, including: binding energy distribution, neighbor distribution function, bond angle distribution, cluster size distributions for different C–C bond lengths, and percolation threshold. Analysis of microscopic configurations revealed that the network structure of the studied amorphous diamond-like carbon lacks any graphitic fragments (i.e., regular hexagons with a 120° C–C–C bond angle). We found that for the assumed C–C bond length ≤ 1.42 Å (i.e., sp2 hybridization), the carbon network is poorly connected with a 70% contribution from isolated carbon atoms. The percolation threshold corresponds to a C–C bond length ≤ 1.52 Å, which is close to 1.54 Å (i.e., C–C bond length in perfect diamond). This finding is consistent with experimental high levels of tetrahedral bonding (i.e., sp3 hybridization) reported for high density tetrahedral amorphous carbons (i.e., sp3 fraction of 80–85%). Thus, we concluded that the HRMC method complemented with cluster size analysis and determination of percolation threshold is a promising methodology in studies of ill-defined carbonaceous materials.